2021
DOI: 10.2147/opto.s303286
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Retinoscopy, Autorefractometry and Subjective Refraction for Determining Refractive Errors in Congolese Children

Abstract: Objective: To assess the agreement between retinoscopy and autorefractometry and between subjective refraction and both retinoscopy and autorefractometry in Congolese children.Patients and Methods: Fifty-four children (6-17 years old) were enrolled consecutively in this cross-sectional study. Refraction was evaluated before and after cycloplegia (1% cyclopentolate) with retinoscopy and autorefractometry. Readings were compared (paired t-test) and agreement assessed with Bland-Altman plots. Subjective refractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Several studies on children have shown that lack of cycloplegia is associated with a slight overestimation of myopia and marked errors in estimates of the prevalence of emmetropia and hyperopia [5]. In clinical practice, cycloplegic autorefraction and retinoscopy are recommended for children [17][18][19]. Consequently, we first compared BWFOM refraction with autorefraction and retinoscopy under cycloplegia to determine its accuracy for children's refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on children have shown that lack of cycloplegia is associated with a slight overestimation of myopia and marked errors in estimates of the prevalence of emmetropia and hyperopia [5]. In clinical practice, cycloplegic autorefraction and retinoscopy are recommended for children [17][18][19]. Consequently, we first compared BWFOM refraction with autorefraction and retinoscopy under cycloplegia to determine its accuracy for children's refraction.…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by the impossibility of using cycloplegics in screenings during objective refraction, adopting static refraction with the use of a Keeller Professional Streak Retinoscope and subjective refraction to avoid overestimating the prevalence of myopia. Studies have shown that non-cycloplegic retinoscopy and subjective refraction are clinically accurate and can be applied to screening for refractive error in children, showing good agreement with cycloplegic refraction [45,46]. Furthermore, due to the difficulty of performing repeated measurements among children during the program, due to the limited time of the program, a reliability study using intra-and inter-observer measures was not performed…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to accurately measure refractive status in children as overestimation or underestimation of error causes accommodative stress, which increases the risk of amblyopia (Lei et al, 2023). Several methods, such as photorefraction, autorefractometry, retinoscopy, and subjective refraction, are used to measure refractive errors (Mukash et al, 2021). Both auto refractometry and retinoscopy are reliable techniques for assessment of refractive errors.…”
Section: Introductionmentioning
confidence: 99%
“…There may be discrepancies among the final objective corrective achieved with retinoscopy, autorefraction (AR), and subjective refraction accepted by the patient. The previous studies are inconclusive regarding determining the most accurate technique for subjective correction (Kedia and Baruah, 2022;Magome et al, 2021;Mukash et al, 2021). These discrepancies can be due to various factors such as the age of the patients, differences in autorefractors, the experience of the operator performing retinoscopy, and cycloplegic use (Mohana Priya et al).…”
Section: Introductionmentioning
confidence: 99%